2006
DOI: 10.1073/pnas.0601682103
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Su48, a centrosome protein essential for cell division

Abstract: The centrosome functions as the major microtubule-organizing center and plays a vital role in guiding chromosome segregation during mitosis. Centrosome abnormalities are frequently seen in a variety of cancers, suggesting that dysfunction of this organelle may contribute to malignant transformation. In our efforts to identify the protein components of the centrosome and to understand the structure features involved in the assembly and functions of this organelle, we cloned and characterized a centrosome-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…A previous study reported that misexpression of ZNF365 led to cytokinesis failure, suggesting that its deregulation may contribute to the development of genomic instability during tumorigenesis [46]. Of high relevance to our findings, recent genome-wide association studies have identified SNPs within ZNF365 that bear significant correlation with breast cancer susceptibility [47].…”
Section: Discussionsupporting
confidence: 70%
“…A previous study reported that misexpression of ZNF365 led to cytokinesis failure, suggesting that its deregulation may contribute to the development of genomic instability during tumorigenesis [46]. Of high relevance to our findings, recent genome-wide association studies have identified SNPs within ZNF365 that bear significant correlation with breast cancer susceptibility [47].…”
Section: Discussionsupporting
confidence: 70%
“…Regulation of Cytokinesis by Lats2-Recently, it has been reported that a number of novel centrosomal proteins such as Cep55 and Su48 regulate cytokinesis in mammalian cells (81,82). We have shown here that, like these centrosomal proteins, the centrosomal protein Lats2 localizes at the midbody during late mitosis and plays a role in cytokinesis.…”
Section: Embryonic Lethality Of a Total Lats2 Knockout In Mouse Ismentioning
confidence: 60%
“…This gene has a complex pattern of alternative splicing and transcriptional start sites [137]. Wang et al [138] found that ZNF365A localizes to the centrosome throughout the cell cycle in several human cell lines. A mutation analysis demonstrated that the centrosomal localization of ZNF365A requires 2 coiled-coil subdomains but not the C-terminal zinc finger structure.…”
Section: Discussionmentioning
confidence: 98%